Photovoltaic charging of a lead-acid battery using a buck-boost converter - Fernando, Marco L.
The sun is a very powerful source of energy. Harnessing this energy will be a big step towards a cleaner power generation. This project aims to create an efficient battery charger circuitry. This circuit will be designed particularly to work under conditions frequently experienced in the Philippines. A buck-boost converter will be used to control the charging voltage of the battery.